Sustainability-based evaluation of casting gating systems: A multi-criteria decision-making approach - Papanikolaou, Michail; Pagone, Emanuele; Salonitis, Konstantinos; Jolly, Mark R. (Elsevier, 2020)
The selection of the most appropriate casting gating system design is one of the most critical decision-making tasks in foundries as it is closely associated to the amount of air inclusions and surface defect concentration, which should be minimal in the final casting product to ensure superior quality and enhanced mechanical properties. Moreover, the design of the gating system influences the material and energy usage and consequently the cost of the sand casting manufacturing process. Therefore, its design should be thoughtfully considered and planned. In this investigation, Multi-Criteria Decision-Making (MCDM) is being coupled with Computational Fluid Dynamics (CFD) simulations in order to select the optimal gating system design with respect to the sustainability of the process. Besides process energy, three additional criteria were used for the evaluation of the gating system performance, namely: air entrainment, surface defect concentration and mould cost. CFD simulations were performed to evaluate each one of the 6 gating system designs considered against each one the aforementioned criteria. The selection of the most appropriate gating system was performed using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS).
Keywords: Gating System Design; Sand casting; Computational fluid dynamics (CFD); TOPSIS; Multi-criteria decision-making (MCDM)